Structural Optimization of Hydrogenated Amorphous Silicon Layers for Enhanced Solar Cell Efficiency - Soni Prayogi; Nmenakota Benony Etwiory; Muhammad A (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Energy conversion efficiency of hydrogenated amorphous silicon (a-Si: H) based solar cells remains a major challenge in the development of renewable energy technologies. One approach to improve this efficiency is through improving the solar cell layer structure. This research aims to maximize the layer structure of a-Si: H solar cells by using OghmaNano software simulation. This simulation allows in-depth analysis of the effect of bandgap variation as well as layer thickness on solar cell performance. The method used in this research is to perform numerical simulations using OghmaNano software. The a-Si: H solar cell model was built by varying relevant parameters such as substrate (glass), ITO, p i n layer, and metal contacts. Simulations were performed to obtain the I-V characteristics of the solar cell, which were then used to calculate the energy conversion efficiency. The simulation results were analyzed to identify the layer structure configuration that yielded the highest efficiency. The results hypothesize that determining the layer structure of a- Si: H solar cells can significantly improve the energy conversion efficiency. Variations in intrinsic layer thickness and bandgap have a significant effect on solar cell performance. With variations in layer thickness and bandgap, it is expected to maximize light absorption and increase energy conversion efficiency, which will significantly improve the overall performance of solar cells.